2020
DOI: 10.1101/2020.11.01.356071
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Effects of external stimulation on psychedelic state neurodynamics

Abstract: Recent findings have shown that psychedelics reliably enhance brain entropy (understood as neural signal diversity), and this effect has been associated with both acute and long-term psychological outcomes such as personality changes. These findings are particularly intriguing given that a decrease of brain entropy is a robust indicator of loss of consciousness (e.g. from wakefulness to sleep). However, little is known about how context impacts the entropy-enhancing effect of psychedelics, which carries import… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
66
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
2

Relationship

4
6

Authors

Journals

citations
Cited by 38 publications
(87 citation statements)
references
References 58 publications
(80 reference statements)
10
66
3
Order By: Relevance
“…Recent findings by Mediano et al (2020) provide strong quantitative evidence on how environmental conditions have a substantial influence on neural dynamics during a psychedelic experience in humans. This work showed how brain entropy is modulated by stimulus manipulation during a psychedelic experience by studying participants under the effects of LSD or placebo, either with gross state changes (eyes closed vs. open) or different stimulus (no stimulus vs. music vs. video).…”
Section: Discussionmentioning
confidence: 99%
“…Recent findings by Mediano et al (2020) provide strong quantitative evidence on how environmental conditions have a substantial influence on neural dynamics during a psychedelic experience in humans. This work showed how brain entropy is modulated by stimulus manipulation during a psychedelic experience by studying participants under the effects of LSD or placebo, either with gross state changes (eyes closed vs. open) or different stimulus (no stimulus vs. music vs. video).…”
Section: Discussionmentioning
confidence: 99%
“…This would shed light on how the low-level features modulated the brain dynamics, since in this study we focused more on the semantic features of the stimulation. Moreover, the careful investigation of how and to what extent DeepDream can be compared to actual altered experience would have a considerable impact on the field of psychedelic research, especially in light of recent findings suggesting an important role of the external stimulation on the brain dynamics of hallucinatory states [ 43 ]. Since DeepDream, by definition, mimics hallucinatory perception using external stimulation, it would be interesting to use it as a tool to further explore this aspect of psychedelic brain dynamics.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, while shamanic practitioners kept their eyes closed during shamanic drumming, methodology varied across the studies included by Studerus et al ( 2010 ). Recent literature examining the impact of external stimulation during the psychedelic state found that the greatest changes in brain activity (i.e., brain entropy) occurred during eye closure (Mediano et al, 2020 ). Thus, the heightened OAV scores in shamanic practitioners compared to those of individuals under the influence of psychedelics may be due to the inclusion of less intense experiences due to eye-opening.…”
Section: Methodologic Strengths and Weaknessesmentioning
confidence: 99%